Ethical arguments that support intentional animal killing - Allen, Benjamin L.; Abraham, Andrew J.; Arlinghaus, Robert; Belant, Jerrold L.; Blumstein, Daniel T.; Bobier, Christopher; Bodenchuk, Michael J.; Clauss, Marcus; Dawson, Stuart J.; Derbyshire, Stuart W. G.; Ferreira, Sam M.; Fleming, Peter J. S.; et al. (Frontiers in Ecology and Evolution, 2025)
Killing animals is a ubiquitous human activity consistent with our predatory and competitive ecological roles within the global food web. However, this reality does not automatically justify the moral permissibility of the various ways and reasons why humans kill animals – additional ethical arguments are required. Multiple ethical theories or frameworks provide guidance on this subject, and here we explore the permissibility of intentional animal killing within (1) consequentialism, (2) natural law or deontology, (3) religious ethics or divine command theory, (4) virtue ethics, (5) care ethics, (6) contractarianism or social contract theory, (7) ethical particularism, and (8) environmental ethics. These frameworks are most often used to argue that intentional animal killing is morally impermissible, bad, incorrect, or wrong, yet here we show that these same ethical frameworks can be used to argue that many forms of intentional animal killing are morally permissible, good, correct, or right. Each of these ethical frameworks support constrained positions where intentional animal killing is morally permissible in a variety of common contexts, and we further address and dispel typical ethical objections to this view. Given the demonstrably widespread and consistent ways that intentional animal killing can be ethically supported across multiple frameworks, we show that it is incorrect to label such killing as categorically unethical. We encourage deeper consideration of the many ethical arguments that support intentional animal killing and the contexts in which they apply.